Faktor-Faktor Yang Mempengaruhi Kepatuhan Wajib Pajak Pajak Bumi dan Bangunan - Nurmalia Indria Ananda; Veronika Sari Den Ka; Imron Burhan (PT Bone Jaya Kreatif, 2022)
Land and Building Tax (PBB) is a tax imposed on the ownership or utilization of land and buildings. The UN is a Central Tax in which almost all realizations of UN revenues are handed over to local governments, both provincial and regency/city, under Law No. 28 of 2009 concerning regional taxes and regional levies. The purpose of this study is to find out the factors that affect taxpayer PBB compliance in Bulurokeng Village. This research uses quantitative methods. The data used in this study are secondary data from journals, books, and internet sites.The number of samples in this study wa 128 taxpayer PBB in Bulurokeng Village. Data analysis using SPSS 25. The results showed that the intention to comply did not have a significant effect on the compliance of UN taxpayers in Bulurokeng Village. Sanctions do not have a significant effect on taxpayer compliance in Bulurokeng Village. Nationalism has no significant effect on taxpayer compliance in Bulurokeng Village. The trust of the government and the law not shown a significant effect on taxpayer compliance in Bulurokeng Village. The level of compliance of UN taxpayers in Bulurokeng Village has not been effective in the implementation of the functions of intention to comply, sanctions, nationalism, and the trust of the government and law in paying the UN. Basically, UN taxpayers in Bulurokeng Village have not shown a form of compliance in paying the UN because there is no intention in individuals to comply, the sanctions imposed cannot change the taxpayer's view to comply, the spirit of nationalism towards the state still needs to be developed in building the country, and government and legal trust has not been able to influence the taxpayer's mindset on the importance of UN taxes to build a government.